THE CHEMICAL PROCESSES OCCURRED IN THE REMOVAL OF POLYCYCLIC AROMATIC HYDROCARBONS (PAHS) ON THE SOIL BY FENTON'S REAGENT - NURSIAH LA NAFIE, (International Journal of Pharma and Bio Sciences, 2014)
The chemical processes occurred in the decomposition of polycyclic aromatic hydrocarbons (PAHs) in the soil by Fenton’s Reagent have been investigated. The aim of this work was to determine the intermediate products of PAHs oxidation by Fenton’s Reagent. The organic material after oxidation was separated into neutral and acidic fraction. Acidic compounds were converted to methyl esters by reaction with diazomethane, and were analysed by using GC/MS. The result showed that a single Fenton’s oxidation cycle was clear a reduction occurred, typically mono- and dicarboxylic acids, remain, and would in themselves continue to pose an environmental hazard unless removed by further oxidation. The neutral material contained PAHs as well as oxidized product.